“Nga-wayang”: A New Dance Creation from a Globalized Sociocultural Environment - Ni Putu Ari Sidiastini; I Wayan Rai S; Ni Made Ruastiti (Journal of Aesthetics, Creativity and Art Management, 2022)
This scientific article aims to discuss a new dance creation entitled “Nga-wayang”, whose creation idea depicts the character Gatot Kaca in a two-dimensional wayang kulit show. No one has worked on a dance that was transformed from a two-dimensional wayang kulit performance into a new three-dimensional dance creation. The creation of the “Nga-wayang” dance uses qualitative methods. The creation process is carried out in stages: ngarencana, nuasen, makalin, nelesin, and ngebah. The search for ideas was carried out using participatory observation techniques and in-depth interviews with related parties. The deepening of the character of Gatot Kaca's character is carried out through library research and discography. The process of creating this new dance creation is carried out using transformation theory and aesthetic theory. The cultivation of this work of art has resulted in a new dance creation entitled “Nga-wayang”. As a new dance creation, “Nga-wayang” is presented full of new ideas based on the influence of the art ecosystem in the influence of globalization in terms of poses, variety of movements, techniques, dynamics, tempo, and level play based on multimedia such as LCD projectors, LED lights, and smoke. The process of composing this dance has been carried out since this material was developed as a final choreography class assignment, the presentation of which has been continuously refined. “Nga-wayang” is a new dance creation that departs from the experience of the cultural environment in the era of globalization, namely the ecosystem as an art reinforcement.